2015
DOI: 10.3390/mi6101429
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Surface Modification of PDMS Microchannel for O/W and W/O/W Emulsions

Abstract: A surface modification method for bonded polydimethylsiloxane (PDMS) microchannels is presented herein. Polymerization of acrylic acid was performed on the surface of a microchannel using an inline atmospheric pressure dielectric barrier microplasma technique. The surface treatment changes the wettability of the microchannel from hydrophobic to hydrophilic. This is a challenging task due to the fast hydrophobic recovery of the PDMS surface after modification. This modification allows the formation of highly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…So far, many surface treatment methods have been proposed to modify and increase the hydrophilicity of PDMS, including UV reactions, UV/ozone reactions, UV grafting, laser/plasma etching, chemical surface treatments, surface casting, and corona discharges, just to mention a few. However, these reported procedures have various disadvantages which include safety problems, complex processes, time consumption as well as requiring well‐trained technicians to perform them.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many surface treatment methods have been proposed to modify and increase the hydrophilicity of PDMS, including UV reactions, UV/ozone reactions, UV grafting, laser/plasma etching, chemical surface treatments, surface casting, and corona discharges, just to mention a few. However, these reported procedures have various disadvantages which include safety problems, complex processes, time consumption as well as requiring well‐trained technicians to perform them.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Apart from its extensive use in low-pressure plasma polymerization, W/FM is currently used by several research groups as a deposition parameter for atmospheric pressure plasma polymerization, [13][14][15][16][17][18][19][20][21] where the precursor is diluted in an inert gas. This preliminary work challenges the use of the W/FM parameter for atmospheric plasma as used by several authors, [13][14][15][16][17][18][19][20][21] including the present authors, and opens new lines of inquiry in the further study of plasma parameters at atmospheric pressure. 12 In this work, allyl methacrylate (AMA) was deposited by means of an atmospheric plasma Dielectric Barrier Discharge (DBD).…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Ion-exchange chromatography is one of the most efficient methods for systematically studying the separation selectivity of ions. [10] This method has allowed us to analyze the effects of various factors, such as ion-exchange group structures, [11][12] solvents, [13] types of coexisting ions, [14][15][16] and temperatures, [2,9,[14][15]17,18] on ion-exchange selectivity. For example, anion-exchange selectivity in water increases with an increase in the size of naked anions, regardless of the structure of the anion-exchange groups (e. g. Cl À < Br À < I À < ClO 4 À ).…”
mentioning
confidence: 99%
“…It has been shown that the type of eluent ion has a greater impact on ionexchange selectivity compared to the structure of ionexchange groups in some cases. [14][15][16] Structural information that was obtained from resins with a single type of counterion may be inapplicable to the discussion of chromatographically evaluated ion-exchange separation selectivity.…”
mentioning
confidence: 99%